If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -6y + 33 = 0 Reorder the terms: 33 + 9x + -6y = 0 Solving 33 + 9x + -6y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-33' to each side of the equation. 33 + 9x + -33 + -6y = 0 + -33 Reorder the terms: 33 + -33 + 9x + -6y = 0 + -33 Combine like terms: 33 + -33 = 0 0 + 9x + -6y = 0 + -33 9x + -6y = 0 + -33 Combine like terms: 0 + -33 = -33 9x + -6y = -33 Add '6y' to each side of the equation. 9x + -6y + 6y = -33 + 6y Combine like terms: -6y + 6y = 0 9x + 0 = -33 + 6y 9x = -33 + 6y Divide each side by '9'. x = -3.666666667 + 0.6666666667y Simplifying x = -3.666666667 + 0.6666666667y
| 1-3k=8-2k | | 25-5x=30 | | 7(5-r)=-6r+40 | | 4/5=3 | | Oh/t=12r | | 18x-240=15x | | 8/27*9/42 | | -29=-7x-4(-3x-4) | | y=-3/5(5)+3 | | 10m^2+60m= | | 1+2p-6=p-13 | | t-r=m | | y=-3/5(4)+3 | | y=-3/5(3)+3 | | 36+14x=9 | | 3b-2a=6t+a-4b | | 6r+1=18r-2r | | y=-3/5(2)+3 | | -5x+8=6x-47 | | 5(x-2)-9=1-5x | | 15x+12=4x+45 | | 2(x-5)+2x=4(x+9)-46 | | 2+(5+2)= | | -13=4-3a+1 | | (3-6n^2-8n^4)-(-6n^4-3n-8n^5)=0 | | -16=32x | | 4x-2b=5x+a | | 2.8=n/4 | | 3x+4=-19 | | 1/2)8-6h)=h | | 6x-16-3x=7x-9 | | y=-3/5(1)+3 |